1994
DOI: 10.1073/pnas.91.14.6329
|View full text |Cite
|
Sign up to set email alerts
|

Central effects of baroreceptor activation in humans: attenuation of skeletal reflexes and pain perception.

Abstract: Activating (4), induce synchronization of the electroencephalogram (5), increase cortical positivity (6), blunt pain sensations (7), reduce anxiety (8, 9), and induce sleep (10) or even clinically significant syncope (11). Arousing emotional and pain stimuli elevate blood pressure (12)(13)(14)(15)(16)(17)(18), and the central nervous system (CNS) inhibitory effects ofbarostimulation most simply can be seen to provide supplementary negative feedback, which, along with cardioinhibition and vasodilatation, helps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
141
2
5

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(156 citation statements)
references
References 24 publications
8
141
2
5
Order By: Relevance
“…Although the current study suggests that the baroreflex may be the mechanism linking pain and blood pressure, our study design prevents us from determining whether this is due to a peripheral or central effects. Although previous research, in non-exercise settings, has suggested a central effect of baroreflex stimulation, [36][37][38] it is also possible that there may be a direct peripheral mechanism, a pathway that cannot be discounted by the current study. This is further complicated by the inherent problems of measuring spontaneous baroreflex sensitivity during exercise (i.e., the inability to measure the full function curve).…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Although the current study suggests that the baroreflex may be the mechanism linking pain and blood pressure, our study design prevents us from determining whether this is due to a peripheral or central effects. Although previous research, in non-exercise settings, has suggested a central effect of baroreflex stimulation, [36][37][38] it is also possible that there may be a direct peripheral mechanism, a pathway that cannot be discounted by the current study. This is further complicated by the inherent problems of measuring spontaneous baroreflex sensitivity during exercise (i.e., the inability to measure the full function curve).…”
Section: Discussioncontrasting
confidence: 40%
“…In concordance with this, previous research has found links between baroreflex sensitivity and the hypertension-hypoalagesia phenomenon. [36][37][38] For example, cardiac cycle synchronized acute baroreceptor stimulation 37 and natural activation of baroreceptors 36 produced decreased pain perception in humans. However, it is also possible that other mechanisms, possibly in conjunction with baroreflex dysregulation, may play a role in the blood pressure-pain relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the observation of arousal and pain dampening exerted through baroreceptor activation, Dworkin, Rau, Elbert and colleagues (Dworkin, 1988;Rau and Elbert, 1993;Elbert et al, 1994;Dworkin et al, 1994Dworkin et al, , 2000 advanced the model of 'learned hypertension'. This theory predicts that learning mechanisms, and operant conditioning in particular, contribute to blood pressure elevations with a possibly catastrophic outcome.…”
Section: Significance Of the Baroreceptor -Brain Circuitry For A Modementioning
confidence: 99%
“…[1][2][3][4][5][6] Experimental studies have also demonstrated a link between the baroreceptor function and pain perception. [7][8][9][10][11] Modulatory interactions between pain sensitivity and the cardiovascular system have been reported both in physiological conditions and in patients with various cardiovascular syndromes. Alterations in pain sensitivity and circulating ␤-endorphin, an endogenous opioid-like peptide, were found in hypertensive subjects, patients with shock and heart failure, and subjects with silent myocardial ischemia.…”
mentioning
confidence: 99%